If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(2x-5)+9=8(5x-2)+1
We move all terms to the left:
7(2x-5)+9-(8(5x-2)+1)=0
We multiply parentheses
14x-(8(5x-2)+1)-35+9=0
We calculate terms in parentheses: -(8(5x-2)+1), so:We add all the numbers together, and all the variables
8(5x-2)+1
We multiply parentheses
40x-16+1
We add all the numbers together, and all the variables
40x-15
Back to the equation:
-(40x-15)
14x-(40x-15)-26=0
We get rid of parentheses
14x-40x+15-26=0
We add all the numbers together, and all the variables
-26x-11=0
We move all terms containing x to the left, all other terms to the right
-26x=11
x=11/-26
x=-11/26
| (0.25)^3-0.5x^2=8 | | 5x−4=x+8 | | 5x+2/3=2x+3/4 | | 8(c-6)=3c+10) | | 37-42u=-43u+45 | | 3x=+2x+3 | | 3q-16=-31 | | -52n-135=-44n-87 | | 11+52y=49y-13 | | -32z+17=53-36z | | 59+40t=-21+30t | | -174-50d=-42d-94 | | -34-39m=-40m-43 | | -7r+5=-5-2r | | 7x+5/9=1 | | 2x+34=x-23 | | 3x=179.5 | | -2x+3X2=4 | | 3x+4=5+6+8 | | 0.7x+13=15,8 | | 7y+3=30-2y | | 5x+2X2=3 | | 27-7w=2w | | x(4+3)=70 | | x×5÷10=3 | | (2x+1)/3=x-2 | | 20-5(x-2)=2(x+3)-3(7-x)-4 | | 2t-4t-7=9 | | 4(x+2)+3x=7x+18 | | 7x+6=7.75 | | 4(11-3c)=-124 | | 3(x+4)=4(x-1)+14 |